Reflective Pedagogical Mediation and Value Formation in Digital Islamic Education: Longitudinal Evidence from Religious Attitude Development - Rodhatul Jennah; Aan Hasanah; Mazrur Mazrur; Surawan Surawan (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Research on digital learning in Islamic education has predominantly emphasized short-term instructional outcomes, providing limited understanding of how digitally mediated learning influences students’ religious attitudes over time, particularly in non-Western educational contexts. Moreover, the pedagogical processes through which digital environments facilitate value internalization remain underexplored. This study investigated the longitudinal development of students’ religious attitudes in digital Islamic education, with particular attention to the role of reflective pedagogical mediation. Employing a quantitative longitudinal quasi-experimental design, the study followed 120 madrasah students across three measurement points: initial, midpoint, and final. Data were collected using a validated 18-item Likert-scale questionnaire and analyzed through repeated measures ANOVA and independent-samples t-tests. The findings revealed a significant and gradual improvement in students’ religious attitudes throughout the study period. Students who experienced digitally mediated learning supported by reflective and value-oriented pedagogy demonstrated greater attitudinal gains than those exposed to more instructional, non-reflective approaches. Although positive changes were sustained over time, the rate of improvement slowed during the later stages of the intervention. These findings suggest that the educational value of digital learning depends less on technological exposure itself than on pedagogical processes that promote reflection and engagement with religious values. The study contributes longitudinal evidence to the emerging field of digital religious education by identifying reflective pedagogical mediation as a mechanism associated with sustained value formation and offers practical insights for aligning digital innovation with the broader aims of moral and religious development.